Complete mitochondrial genome and the phylogenetic position of the White-spotted guitarfish Rhynchobatus australiae (Rajiformes, Rhinobatidae) - Si, Ranran (Mitochondrial DNA B Resour, 2016)
We first determined the complete mitochondrial genome of the White-spotted guitarfish Rhynchobatus australiae (Rajiformes, Rhinobatidae). The complete mitogenome was 16,804 bp, with a base composition of 32.3% A, 27.5% T, 26.9% C and 13.3% G, containing 13 protein-coding genes, two rRNAs, 22 tRNAs and a control region (D-loop). It had 35 bp short intergenic spaces and 39 bp overlaps between genes. The gene order and composition of R. australiae was similar to most other fishes. The codon usage followed the typical vertebrate mitochondrial pattern (ATG or GTG for start codon and TAA or T for stop codon). The phylogenetic result showed that R. australiae was clustered with the Rhinobatos.